Antinociceptive Effect of an Aqueous Extract and Essential Oil from Baccharis heterophylla - Erika Castillejos-Ramírez; Araceli Pérez-Vásquez; Rafael Torres-Colín; Andrés Navarrete; Adolfo Andrade-Cetto; Rachel Mata (Plants, 2021)
Infusions and poultices prepared from the aerial parts of Baccharis heterophylla Kunth (Asteraceae) are widely used in Oaxaca (Mexico) for relieving painful and inflammatory complaints. Therefore, the antinociceptive potential of an aqueous extract (31.6–316 mg/kg, p.o.) and essential oil (30–177 µg/paw, i.pl.) of the plant was assessed using the formalin test. Both preparations inhibited the formalin-induced nociception response (100–316 mg/kg and 100–177 µg/paw, respectively) during the test’s second phase. Chemical analysis of the aqueous extract revealed that the major active components were chlorogenic acid (1), 3,4-di-O-(E)-caffeoylquinic acid (2), 3,5-di-O-(E)-caffeoylquinic acid (3), 4,5-di-O-(E)-caffeoylquinic acid (4), 3,5-di-O-(E)-caffeoylquinic acid methyl ester (5), apigenin (6), genkwanin (7), acacetin (8). Compounds 1–5 and 8 are new for B. heterophylla. A high-pressure liquid chromatographic method for quantifying chlorogenic acid (1) and di-caffeoylquinic acids 2–4 in the plant was developed and validated. Analyses of the essential oil and the headspace solid-phase microextraction products, via gas-chromatography-mass spectrometry, revealed that the major volatiles were β-pinene, myrcene, D-limonene, β-caryophyllene, and α-caryophyllene, which have demonstrated antinociceptive properties.